A Comparison of Algorithms for Controller Replacement in Software Defined Networking - T T, Anitson; Vinod, Smitha (International Journal of Engineering and Technology, 2018)
Software Defined Network (SDN) partitions the control plane and the information plane to decrease the cost and for increasing the capacity for upgrading, and this will be helpful for the network administrators to manage the network services. Itâ€™s the location where the controller exists. One of the main issue in Software Defined Networking is the location of the controllers as this could affect network execution and cost. In this paper, we have done an analysis on some algorithms that have been used for minimizing the number of controllers to reduce the latency, delay, etc. while placing a controller with the consideration of communication among the controller and the nodes.Â